The Foreign Direct Investment Policy Which Reflects the Proportional Protection - Yuniarti Yuniarti; Muchammad Zaidun (Yuridika, 2019)
Investment law is an urgently required regulation to regulate an investment activity. Hence the formulation within those laws has not yet provided a balance protection for all parties; those are the home countries, host countries and investors. The investment law itself regulate by 3 different kinds of laws, that is the customary international law, national law and contract law. Regulating investment activities in host states will have to consider the customary international law, as the international framework. This law is applicable due to the different jusrisdiction involved within the business activities. Indonesia investment law regulation firstly introduced by law number 1/1967 concerning foreign direct investment. Subsequently, it was amended by law number 25/2007 concerning Investment Law. However, some research has to be carried out regarding the protection of the parties. This research analysed the principle of proportionality interest protection to provide a fair protection of parties. Eventually, the protection of the state as host country and investors as the alien in host country.This research is a normative legal research, which use statute approach, historical approach and conceptual approach to determine the principle that could be used to maximize the protection of actors within the investment activities in Indonesia.